Numeric Rating Scales Show Prolonged Post-exertional Symptoms After Orthostatic Testing of Adults With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - van Campen, C (Linda) M. C.; Rowe, Peter C.; Verheugt, Freek W. A.; Visser, Frans C. (Frontiers in Medicine, 2021)
Introduction: Muscle pain, fatigue, and concentration problems are common among individuals with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). These symptoms are commonly increased as part of the phenomenon of postexertional malaise (PEM). An increase in the severity of these symptoms is described following physical or mental exercise in ME/CFS patients. Another important symptom of ME/CFS is orthostatic intolerance, which can be detected by head-up tilt testing (HUT). The effect of HUT on PEM has not been studied extensively. For this purpose, we assessed numeric rating scales (NRS) for pain, fatigue, and concentration pre- and post-HUT. As pain is a core symptom in fibromyalgia (FM), we subgrouped ME/CFS patients by the presence or absence of FM. Methods and Results: In eligible ME/CFS patients who underwent HUT, NRS of pain, fatigue, and concentration were obtained pre-HUT, immediately after HUT, at 24 and 48 h, and at 7 days posttest. We studied 174 ME/CFS patients with FM, 104 without FM, and 30 healthy controls (HC). Values for all symptoms were unchanged for HC pre- and post-HUT. Compared with pre-HUT, the three NRS post-HUT were significantly elevated in both ME/CFS patient groups even after 7 days. NRS pain was significantly higher at all time points measured in the ME/CFS patients with FM compared with those without FM. In ME/CFS patients, the maximum fatigue and concentration scores occurred directly post-HUT, whereas pain perception reached the maximum 24 h post-HUT. Conclusion: NRS scores of pain, fatigue, and concentration were significantly increased even at 7 days post-HUT compared with pre-HUT in ME/CFS patients with and without FM, suggesting that orthostatic stress is an important determinant of PEM.